Benefit Incidence of Public Spending on Health in the Philippines - Rosario G. Manasan; Janet S. Cuenca (Philippine Institute for Development Studies (PIDS), 2010)
Directing government subsidies to social services such as health care is expected to bring about positive external/social benefits and improve equity in access to health services. In general, government spending on health is envisioned to improve the well-being of beneficiaries and enhance their capability to earn income in the future. Given this perspective, the question that this paper addresses is: to what extent have the poor benefited from publicly provided health services? In particular, it attempts to assess whether government expenditure on health sector had a redistributive impact by making use of benefit incidence analysis.
Keywords: 330; targeting; poverty reduction; Philippines; benefit incidence analysis; Gini coefficient; concentration coefficient; concentration curve; public health; hospital care/services; Gesundheitsfinanzierung; Gesundheitsversorgung; Armutsbekämpfung; Philippinen